Portfolio theory, job choice and the equilibrium structure of expected wages - Mayers, David (Journal of Financial Economics, 1974)
This paper presents some of the implications of modern portfolio theory for the equilibrium structure of wages under conditions of uncertainty. The primary model presented is a model of wage uncertainty and hence the equilibrium structure is derived in terms of expected wages. The equilibrium structure with the assumption of a perfect labor market (e.g., labor units are infinitely divisible and costlessly mobile) and a perfect capital market is shown to have a very simple linear form. The model assumes homogeneous labor units as well as the usual single-period capital asset pricing model assumptions.